Identification of Landslide-Prone Areas Using Drones and Geoelectricity in Gang Sakal, Panjang District, Bandar Lampung - Yanti Lestari (Journal of Applied Science, Engineering and Technology, 2023)
Bandar Lampung City is a densely populated area with a morphology influenced by steep hilly paths. High rainfall can produce hydrometeorological hazards in the form of avalanches. This study aims to examine the material vulnerability of landslides. A combination of topographic mapping using drones and subsurface imaging through ERT geoelectric. Two subsurface profiles were analyzed through the Wenner-Schlumberger configuration with a line length of 120 m and electrode spacing of 5 m. The morphological slope of the drone data processing results is 60 degrees. The dominant subsurface profile has a resistivity of 1 Ωm to >279 Ωm with a depth of 23 m in the first line and a resistivity of 1 Ωm to >343 Ωm with a depth of 23 m in the second line as pyroclastic material. The composition of constituent materials that have not undergone compaction and slope has the possibility of a landslide hazard in the two observed profiles.